We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
316
1
avatar+4 

3n+2 + (3n+3 - 3n+1) = ?

Choices are:

(A) 1/3n+1

(B) 1/3n+2

(C) 3/8

(D) 1/3

 Oct 27, 2018
edited by vivmd  Oct 27, 2018
 #1
avatar+28129 
+2

None of your choices provide the correct solution to what you have written!

 

3n+2 + 3n+3 - 3n+1 → 3n+1(31 + 32 - 30) → 3n+1(3 + 9 - 1) → 11*3n+1 

 

I think you must have meant  3n+2 / (3n+3 - 3n+1)  → 31 / (32 - 30) → 3 / (9 - 1) → 3/8   (where 3n+1 has been factored out of the terms in both numerator and denominator).

 Oct 27, 2018

17 Online Users